Micropropagation of Opuntia and Other Cacti Species Through Axillary Shoot Proliferation: A Comprehensive Review - Bouzroud, Sarah; El Maaiden, Ezzouhra; Sobeh, Mansour; Devkota, Krishna Prasad; Boukcim, Hassan; Kouisni, Lamfeddal; El Kharrassi, Youssef (Frontiers in Plant Science, 2022)
Cacti are one of the most significant and diversified groups of Angiosperms, distributed and cultivated globally, mostly in semi-arid, arid, and the Mediterranean climate regions. Conventionally, they are propagated by seeds or through vegetative propagation via rooted offshoots or grafting. However, these multiplication procedures remain insufficient for mass propagation. In vitro culture techniques are utilized to mass propagate endangered and commercial cacti species. These include somatic embryogenesis and plant regeneration through indirect or direct organogenesis. The latter is a promising tool for commercial clonal propagation of high-value species and has been successfully implemented for several species, such as Mammillaria, Hylocereus, Cereus, Echinocereus, and Ariocarpus. However, its success depends on explant type, basal nutrient formulation of culture medium and types and concentrations of plant growth regulators. This study aimed to assess the potential of in vitro propagation methods applied to Cacti species and discuss the different factors affecting the success of these methods. This study has also highlighted the insufficient work on Opuntia species for mass propagation through axillary buds’ proliferation. The development of an efficient micropropagation protocol is thus needed to meet the supply of increasing demand of Opuntia species for human consumption as fruit, animal feed, and ecological restoration in semi-arid and arid zones.